The Great Divergence in South Africa: Population and Wealth Dynamics over two Centuries - Dieter von Fintel; Johan Fourie (African Economic History Network (AEHN), 2019)
Does wealth persist over time, despite the disruptions of historical shocks like colonisation? This paper shows that South Africa experienced a reversal of fortunes after the arrival of European settlers in the eastern half of the country. Yet this was not, as some have argued was the case elsewhere in colonial Africa, because of an institutional reversal. We argue, instead, that black South Africans found themselves at the mercy of two extractive regimes: those in `white South Africa and those in the `homelands. The political and economic institutions of each of those regimes favoured a small elite: in white South Africa, whites, and in the homelands, the black chiefs and headmen. Democracy brought inclusive institutions for black residents in white South Africa but not for those in the former home- lands. This is why we see mass migration to the urban areas of South Africa today, and why addressing the institutional weaknesses of the former homelands is key to alleviating the poverty in these regions where a third of South Africans still reside.
Keywords: J10; J11; N37; N57; 330; reversal of fortunes; population persistence; institutional reversal; colonial impact; settler economy; African economic history; traditional leaders